Pengaruh Store Image, Store Atmosphere, Brand Association, dan Brand Awarness terhadap Keputusan Pembelian Ulang (Repurchase) (Studi pada Konsumen The Body Shop di Java Mall Semarang) - Mila Azhari; Naili Farida; Saryadi Saryadi (Universitas Diponegoro, 2014)
Intense competition among brands cause a company must have a good marketing strategy and branding right decision, which may encourage customers to make repeat purchases. Store image, store atmosphere, brand association and brand awareness are all factors that are considered by consumers to make the purchase again. Within 3 (three) categories of cosmetic products found fluctuation index of top brand, it shows that in terms of purchasing decisions, the brand experienced a decline. This study aims to determine the effect of store image, store atmosphere, brand association, and brand awareness to re-purchase decisions with a population of 100 respondents taken menggunakam purposive sampling technique. Collecting data using a questionnaire. Measurement scale using Likert scale. Analysis of data using the correlation coefficient, coefficient of determination, regression analysis, t test, and F test using SPSS 20.0. The results of this study show that the variable store image, store atmosphere, brand association, and brand awareness has a positive and significant impact on repeat purchasing decisions. Based on the results of this study, so companies are advised to continue to increase purchases by extending the space inside the store, and increase the variety of products for male consumers.